2019
DOI: 10.1042/bsr20181156
|View full text |Cite
|
Sign up to set email alerts
|

Hemin induces autophagy in a leukemic erythroblast cell line through the LRP1 receptor

Abstract: Hemin is an erythropoietic inductor capable of inducing autophagy in erythroid-like cell lines. Low-density lipoprotein receptor-related protein 1 (LRP1) is a transmembrane receptor involved in a wide range of cellular processes, such as proliferation, differentiation, and metabolism. Our aim was to evaluate whether LRP1 is responsible for hemin activity in K562 cells, with the results demonstrating a three-fold increase in LRP1 gene expression levels (P-values <0.001) when assessed by quantitative real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…This transient nature indicates that hemeinduced barrier disruption is not caused by cell death, and raises the question on which of the signaling pathways involved in the regulation of EB integrity are modulated by heme. This observation is also consistent with a previous study that also showed a dose-dependent effect of heme on EB integrity, and that showed that heme used at a higher concentration (40μM) was associated with a more delayed disruption of EB integrity that was attributed to necroptotic cell death (25), but other pathways that are modulated by heme such as autophagy (47)(48)(49) and MKK3/p38MAPK (50) have also been recently associated with EB changes. It should be noted that our results also confirm that the EB of HUVECs behave similarly to pulmonary and microvascular endothelial cells in response to heme, supporting their use in our subsequent experiments.…”
Section: Discussionsupporting
confidence: 92%
“…This transient nature indicates that hemeinduced barrier disruption is not caused by cell death, and raises the question on which of the signaling pathways involved in the regulation of EB integrity are modulated by heme. This observation is also consistent with a previous study that also showed a dose-dependent effect of heme on EB integrity, and that showed that heme used at a higher concentration (40μM) was associated with a more delayed disruption of EB integrity that was attributed to necroptotic cell death (25), but other pathways that are modulated by heme such as autophagy (47)(48)(49) and MKK3/p38MAPK (50) have also been recently associated with EB changes. It should be noted that our results also confirm that the EB of HUVECs behave similarly to pulmonary and microvascular endothelial cells in response to heme, supporting their use in our subsequent experiments.…”
Section: Discussionsupporting
confidence: 92%
“…We show that depletion of BMP2K variants strongly elevates hemoglobin production upon addition of hemin, a heme precursor which stimulates erythroid differentiation in a manner independent of Tf uptake (Fibach et al, 1987) but involving activation of autophagy (Grosso et al, 2019). Autophagic clearance of intracellular content is indispensable for erythroid differentiation (Cao et al, 2016;Grosso et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…In this study, decreased levels of LRP1 expression at cell surface in monocytes of SCA and IR groups may be related to an accelerated degradation of LRP1 ( 35 ). In this way, different extracellular factors, such as LPS, insulin and hemin, promote the LRP1 degradation through the activation of proteasomal and lysosomal pathways in macrophages and other cells ( 13 , 36 , 37 ). Finally, decreased LRP1 expression at cell surface in monocytes may be due to an increased shedding events in LRP1 at plasma membrane, like those that occur in inflammation by the action of LPS and IFN-γ in macrophages ( 9 ).…”
Section: Discussionmentioning
confidence: 99%